Ageing, migration infrastructure and multi‐generational care dynamics in transnational families. (16th July 2022) - Tu, Mengwei
Abstract: The analysis of transnational family relations from an intergenerational to a multi‐generational perspective highlights the significant role migration infrastructure plays in transnational family care arrangements at different family life stages. Changing migration policies and local‐bound welfare systems in the host and home countries tend to fixate the role of care‐receiver and provider against fluid transnational family care dynamics as the life course of the family unfolds. This paper focuses on Chinese transnational one‐child families in which the initial separation between parents and their only‐child was motivated by the child's overseas education, and followed by the adult child's employment and family formation in the UK. My findings illustrate how reified definitions of the family and familial roles structure mobile individuals' access to family rights in a transnational context. They warn of the danger of entrenched injustice embedded in the definitional classification of family migrants.